The Effects of Aging on Cognitive Motor Control:Functional Connectivity Analysis of Alpha Frequency - Smith, Hunter C (East Carolina University, 2021)
Aging is a natural phenomenon that occurs among humans and can lead to a wide variety of physical and mental changes in individuals. Over 20 percent of the US population is projected to be age 65 and older by the year 2030. This age group will not only face disease and injury, but also the challenges that come along with healthy aging. The process of healthy aging creates physical changes in the makeup and function of the brain. This study is meant to explore the changes in brain connectivity that occur naturally with healthy aging. The data found in this study can be used in future research to compare brain connectivity changes due to stroke with those changes found in healthy adult aging. By creating a baseline of what healthy aging should look like, we can potentially help improve the recovery process for old individuals facing neurological challenges beyond those of healthy aging.
Keywords: Cognitive Motor Control; Aging; Functional Connectivity Analysis